Impacto de la corrupción en el crecimiento económico regional de Perú: Un análisis empírico periodo 2004-2023 - Ñañez Loza, Rolando E. (2024)
The purpose of this article is to analyze and determine the effect of corruption on economic growth at a regional level. Due to the nature of the topic, panel data has been used as an estimation tool for the period 2004-2023 and includes the 24 regions of the country; using the method of pooled regression models, fixed effects model, random effects model and, alternatively, generalized moment models (GMM), finding that corruption can reduce regional GDP by approximately 5.4%.